2018
DOI: 10.1128/jvi.01044-18
|View full text |Cite
|
Sign up to set email alerts
|

The S2 Subunit of Infectious Bronchitis Virus Beaudette Is a Determinant of Cellular Tropism

Abstract: Infectious bronchitis remains a major problem in the global poultry industry, despite the existence of many different vaccines. IBV vaccines, both live attenuated and inactivated, are currently grown on embryonated hen's eggs, a cumbersome and expensive process due to the fact that most IBV strains do not grow in cultured cells. The reverse genetics system for IBV creates the opportunity for generating rationally designed and more effective vaccines. The observation that IBV Beaudette has the additional tropis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 92 publications
(111 reference statements)
2
61
1
Order By: Relevance
“…Bickerton et al reports that three amino acids surrounding the Beaudette S2 cleavage site are determinant of Vero cells and human cells tropism. Introduction of Beaudette-associated amino acids into M41 is sufficient to confer tropism for growth in Vero cells, either by facilitating the binding of virus to additional host attachment factors or by inducing membrane fusion as an additional protease cleavage site (Bickerton et al, 2018). It is widely accepted that the protease cleavage site on S protein is a determinant of coronavirus entry and fusion, and the sequence difference of S protein in various IBV strains may determine not only the cell tropsim but also the entry route/fusion site.…”
Section: Discussionmentioning
confidence: 99%
“…Bickerton et al reports that three amino acids surrounding the Beaudette S2 cleavage site are determinant of Vero cells and human cells tropism. Introduction of Beaudette-associated amino acids into M41 is sufficient to confer tropism for growth in Vero cells, either by facilitating the binding of virus to additional host attachment factors or by inducing membrane fusion as an additional protease cleavage site (Bickerton et al, 2018). It is widely accepted that the protease cleavage site on S protein is a determinant of coronavirus entry and fusion, and the sequence difference of S protein in various IBV strains may determine not only the cell tropsim but also the entry route/fusion site.…”
Section: Discussionmentioning
confidence: 99%
“…The rIBVs BeauR-M41(S), BeauR-M41(S1), BeauR-M41(S2), and BeauR-QX(S1) used here are described in a schematic illustration ( Fig. 1 ) and constructed using the backbone of Beau-R, which is the molecular clone of Beau-CK (accession number AJ311317 ) ( 21 , 25 ). All isolates of IBV and rIBV were propagated in 10-day-old RIR SPF embryonated eggs.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, both rIBVs based on the BeauR backbone acquired the same cell tropism of that of the donor S, M41-CK or 4/91 ( 22 , 23 ). Other work demonstrated that the Beaudette S2 subunit confers the unique ability of Beaudette to replicate in African green monkey kidney (Vero) cells, a continuous cell line licensed for vaccine production ( 24 , 25 ). Vaccination with BeauR-M41(S) or BeauR-4/91(S) can confer protection against homologous challenge based on ciliary activity, reductions in clinical signs and viral load in the trachea at 5 days postchallenge (dpc), further demonstrating the dominant role of the S glycoprotein in inducing protective immunity ( 23 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Like most CoVs, the remaining one third of the genome of IBV encodes four major structural proteins: the spike (S) glycoprotein, the small envelope (E) protein, the membrane (M) glycoprotein, and the nucleocapsid (N) protein. Generally, the S1 subunit of the S glycoprotein is responsible for attachment of the virion to the host cell membrane by interacting with sialic acid, initiating the infection, while the S2 subunit mediates fusion of the virion and cellular membranes by acting as a class I viral fusion protein [5,6]. Two or three small accessory proteins (genes 3, 4 and 5) that vary in number and sequences among IBV strains are interspersed among the genes coding for the structural proteins.…”
mentioning
confidence: 99%